1999
DOI: 10.1177/019791839903300401
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Sexual Behavior and the Risk of HIV in Kenya

Abstract: The association of migration with AIDS in sub-Saharan Africa is well documented, yet the social and behavioral mechanisms underlying this relationship remain poorly understood. Using data from the 1993 Kenya Demographic and Health Survey, this article examines whether migrants are more likely than nonmigrants to have multiple recent sexual partners and not use condoms with those partners. Results indicate that migration is a critical factor in high-risk sexual behavior and that its importance varies by gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
124
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 29 publications
6
124
0
Order By: Relevance
“…This is corroborated by other studies, which demonstrate that young women in rural areas are most likely to experience earlier age of sexual initiation, lower HIV/AIDS knowledge, and higher sexual risk behaviors [30]. Furthermore, as migration patterns in China are characterized as ‘temporary and circular,’ the highest risk groups in this study (rural-to-urban male migrants and rural female non-migrants) may further fuel concerns that young men returning home to girlfriends and wives may serve as agents for the spread of infectious diseases [5, 24, 31].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is corroborated by other studies, which demonstrate that young women in rural areas are most likely to experience earlier age of sexual initiation, lower HIV/AIDS knowledge, and higher sexual risk behaviors [30]. Furthermore, as migration patterns in China are characterized as ‘temporary and circular,’ the highest risk groups in this study (rural-to-urban male migrants and rural female non-migrants) may further fuel concerns that young men returning home to girlfriends and wives may serve as agents for the spread of infectious diseases [5, 24, 31].…”
Section: Discussionsupporting
confidence: 83%
“…This is cause for concern given that migrant males are more likely to report visiting female sex workers [17, 29], and male clients are more likely to be at risk for HIV [17]. Other studies have found lower levels of education, socioeconomic factors, and separation from spouses as risk factors for unprotected sex among male migrants [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Migration is also associated with the rupture and re-establishment of sexual relationships, particularly as many individuals initially migrate without their primary partners. Migration has been identified as a critical factor in high-risk sexual behaviour independent of marital and cohabitation status or social milieu 12. All of these factors suggest that migrants from central and eastern Europe are at risk of sexual ill health and reproductive morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors are likely to have played a part. First, migration has been identified as an independent risk factor for HIV 9. These CEE migrants have taken a risk in coming to the UK and it is thought that such risk-taking may filter through to other areas of their lives 10.…”
Section: Discussionmentioning
confidence: 99%